2020
DOI: 10.15585/mmwr.mm6935a2
|View full text |Cite
|
Sign up to set email alerts
|

Timing of State and Territorial COVID-19 Stay-at-Home Orders and Changes in Population Movement — United States, March 1–May 31, 2020

Abstract: SARS-CoV-2, the virus that causes coronavirus disease 2019 (COVID-19), is thought to spread from person to person primarily by the respiratory route and mainly through close contact (1). Community mitigation strategies can lower the risk for disease transmission by limiting or preventing personto-person interactions (2). U.S. states and territories began implementing various community mitigation policies in March 2020. One widely implemented strategy was the issuance of orders requiring persons to stay home, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
501
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 554 publications
(547 citation statements)
references
References 4 publications
11
501
2
Order By: Relevance
“…Throughout the preceding months, U.S. government officials urged citizens not to buy face masks, but reversed this messaging on April 3 rd to recommend public use of face masks [ 35 ]. Due to these recommendation inconsistencies, unequal access to PPE in the U.S. at the time of data collection, and other research linking psychopathic traits to stockpiling of PPE [ 65 ], our pre-registered analyses focused on the social distancing guidelines and stay-at-home orders that were well established [ 78 ] at the time and affected 94% of the U.S. population [ 31 , 32 ]. Especially because 40.0% of respondents reported never or rarely using PPE in the past week, we suggest caution when drawing conclusions from this variable, as it may simply reflect access to PPE at this particular time point.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the preceding months, U.S. government officials urged citizens not to buy face masks, but reversed this messaging on April 3 rd to recommend public use of face masks [ 35 ]. Due to these recommendation inconsistencies, unequal access to PPE in the U.S. at the time of data collection, and other research linking psychopathic traits to stockpiling of PPE [ 65 ], our pre-registered analyses focused on the social distancing guidelines and stay-at-home orders that were well established [ 78 ] at the time and affected 94% of the U.S. population [ 31 , 32 ]. Especially because 40.0% of respondents reported never or rarely using PPE in the past week, we suggest caution when drawing conclusions from this variable, as it may simply reflect access to PPE at this particular time point.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that stay-at-home mandates limited social mobility and COVID-19 transmission in the U.S. beyond the timeframe of this study, through May and June. 38 , 39 , 40 , 41 However, it remains unclear whether or not adherence to stay-at-home mandates is sustainable long term, or at what point beyond the initial outbreak the costs of these policies begin to outweigh the benefits. 40…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the spread of the virus, health organizations and government officials have recommended reducing physical contact, such as keeping at least six feet of space between oneself and others, commonly referred to as “social distancing”, wearing a mask or other facial covering when in public, and more frequent hand washing [ 3 ]. Nearly all states in the United States issued some type of “stay-at-home” or “shelter in place” order to promote social distancing [ 4 ]. Although the specific rules vary by state, and in some cases, by county within specific states, in general, these orders required or recommended that residents stay home except for essential travel, placed restrictions on large gatherings, and either temporarily closed many businesses or required them to operate at reduced capacity.…”
Section: Introductionmentioning
confidence: 99%